Pengaruh Branding Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Melalui Loyalitas Pelanggan Sebagai Variabel Intervening Pada Cafe Lega Duo Lubuk Alung - M. Taufik Hidayah; Jhon Very; Nilla Pratiwi (CV. ITTC INDONESIA, 2026)
This study aims to determine and analyze the influence of branding and service quality on customer satisfaction through customer loyalty as an intervening variable at Cafe Lega Lubuk Alung. Customer satisfaction at Cafe Lega Lubuk Alung has not yet reached an optimal level, as indicated by customer complaints regarding service quality and the implementation of branding, which in turn affect customer loyalty and satisfaction. This study employed a quantitative research method using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS), with data analyzed using SmartPLS 3.0. The population of this study consisted of all customers of Cafe Lega Lubuk Alung, while the sample was determined using a purposive sampling technique. The results of the study indicate that branding has a significant effect on customer loyalty, service quality has a significant effect on customer loyalty, branding has a significant effect on customer satisfaction, service quality has a significant effect on customer satisfaction, customer loyalty has a significant effect on customer satisfaction, branding has a significant indirect effect on customer satisfaction through customer loyalty as an intervening variable, and service quality also has a significant indirect effect on customer satisfaction through customer loyalty as an intervening variable.